Gal-2 Increases H3K4me3 and H3K9ac in Trophoblasts and Preeclampsia - Laura Hahn; Sarah Meister; Mareike Mannewitz; Susanne Beyer; Stefanie Corradini; Uwe Hasbargen; Sven Mahner; Udo Jeschke; Thomas Kolben; Alexander Burges (Biomolecules, 2022)
Preeclampsia (PE) is a severe pregnancy disorder with a pathophysiology not yet completely understood and without curative therapy. The histone modifications H3K4me3 and H3K9ac, as well as galectin-2 (Gal-2), are known to be decreased in PE. To gain a better understanding of the development of PE, the influence of Gal-2 on histone modification in trophoblasts and in syncytialisation was investigated. Immunohistochemical stains of 13 PE and 13 control placentas were correlated, followed by cell culture experiments. An analysis of H3K4me3 and H3K9ac was conducted, as well as cell fusion staining with E-cadherin and β-catenin—both after incubation with Gal-2. The expression of H3K4me3 and H3K9ac correlated significantly with the expression of Gal-2. Furthermore, we detected an increase in H3K4me3 and H3K9ac after the addition of Gal-2 to BeWo/HVT cells. Moreover, there was increased fusion of HVT cells after incubation with Gal-2. Gal-2 is associated with the histone modifications H3K4me3 and H3K9ac in trophoblasts. Furthermore, syncytialisation increased after incubation with Gal-2. Therefore, we postulate that Gal-2 stimulates syncytialisation, possibly mediated by H3K4me3 and H3K9ac. Since Gal-2, as well as H3K4me3 and H3K9ac, are decreased in PE, the induction of Gal-2 might be a promising therapeutic target.